VOLATILE ANTIDIABETIC PROPERTIES OF PIPER NIGRUM L. ETHANOL EXTRACT (ORIGINAL AND PLANT STEM CELL): NETWORK PHARMACOLOGY STUDY AND ANTIOXIDANT ACTIVITY - RISHA FILLAH FITHRIA; MUHAMMAD BADRUL HUDA; FARAHIDAH MOHAMED; SU LINGYU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to identify and compare the active chemical components in the ethanol extracts of Piper nigrum L. (black pepper) plant and its callus, and to investigate their potential roles in treating diabetes mellitus (DM) through protein–protein interaction (PPI) analysis. Methods: Ethanol extracts were prepared from both the original black pepper plant and its callus. Chemical analysis identified key active substances, including piperine and β-D-glucopyranoside, using retention times (RT). PPI investigations were conducted to determine the interactions involved in diabetes management. The antioxidant capacities of the extracts were assessed using IC50 values, and the biological processes and molecular functions related to diabetes treatment were evaluated. Results: Both the original plant and callus extracts contained active substances such as piperine (37.715%, RT: 28.1967) and β-D-glucopyranoside (54.272%, RT: 16.5768). The primary biological processes identified were the P450 epoxygenase pathway and glycogen production. In addition, the organic acid metabolic process and nucleosome core were implicated in the management of DM by the extracts. The main molecular functions predicted were p53 binding and cyclin. The antioxidant capacities of the extracts were moderate for the callus extract (IC50: 129.92±0.83) and poor for the original plant extract (IC50: 156.69±1.36). Conclusion: The study reveals that the ethanol extracts from the black pepper callus and the original plant possess distinct chemical profiles and mechanisms in treating DM. The callus extract demonstrates a more favorable antioxidant capacity compared to the original plant extract. Both extracts engage in similar biological processes but exhibit differences in their chemical composition and potential therapeutic pathways for diabetes management.